Stepwise Frontal Analysis Coupled with Affinity Chromatography: A Fast and Reliable Method for Potential Ligand Isolation and Evaluation from Mahuang‐Fuzi‐Xixin Decoction. Issue 3 (20th February 2023) - Jin, Yahui; Wang, Wenwen; Zhang, Zilong; Ou, Yuanyuan; Quan, Jia; Zhao, Xinfeng
Abstract: Mahuang‐Fuzi‐Xixin Decoction (MFXD) is widely used in the treatment of asthma, however, the functional components in the decoction targeting beta2‐adrenoceptor (β2 ‐AR) remain unclear. Herein, we immobilized the haloalkane dehalogenase (Halo)‐tagged β2 ‐AR on the 6‐chlorocaproic acid‐modified microspheres. Using the affinity stationary phase, the interactions of four ligands with the receptor were analyzed by stepwise frontal analysis. The association constants were (4.75±0.28)×10 4 M −1 for salbutamol, (2.93±0.15)×10 4 M −1 for terbutaline, (1.23±0.03)×10 4 M −1 for methoxyphenamine, (5.67±0.38)×10 4 M −1 for clorprenaline at high‐affinity binding site, and (2.73±0.05)×10 3 M −1 at low‐affinity binding site. These association constants showed the same rank order as the radioligand binding assay, demonstrating that immobilized β2 ‐AR had capacity to screen bioactive compounds binding to the receptor while stepwise frontal analysis could predict their binding affinities. Application of the immobilized receptor in analysis of MFXD by chromatographic method revealed that ephedrine, aconifine, karakoline, and chasmanine were the bioactive compounds targeting β2 ‐AR. Among them, ephedrine and chasmanine exhibited association constants of (2.94±0.02)×10 4 M ‐1 and (4.60±0.15)×10 4 M −1 to the receptor by stepwise frontal analysis. Molecular docking analysis demonstrated that ephedrine, chasmanine, and the other two compounds interact with β2 ‐AR through the same pocket involving the key amino acids such as Asn312, Asp113, Phe289, Trp286, Tyr316, and Val114. As such, we reasoned that the four compounds dominate the therapeutic effect of MFXD against asthma through β2 ‐AR mediating pathway. This work shed light on the potential of immobilized β2 ‐AR for drug discovery and provided a valuable methodology for rapid screening. Abstract : We developed a fast and reliable method for potential ligand isolation and evaluation targeting beta2‐adrenoceptor from Mahuang‐Fuzi‐Xixin Decoction by stepwise frontal analysis coupled with affinity chromatography. Four ligands, including ephedrine, aconifine, karakoline, and chasmanine were obtained. This may provide a valuable methodology for high throughput screening of the bioactive compounds.